Контактное кольцо - Бекишев Р. Ф. Рудольф Фридрихович; Ениколопов Н. С. Николай Сергеевич; Качин С. И. Сергей Ильич; Лебедев С. И. Сергей Иванович; Ситников С. А. Сергей Александрович; Пролыгин А. П. Анатолий Петрович; Пономаренко А. Т. Анатолий Тихонович; Томлянович Д. К. Давид Карлович
опубл. 15.11.81